(untitled) (Research Journal, 2025)
Agricultural cooperatives play a pivotal role in improving the livelihoods of smallholder farmers by addressing market failures and enhancing access to critical resources such as credit, inputs, and markets. This research paper explores the socio-economic impact of agricultural cooperatives in Ilam Municipality, Nepal. Using a mixed-methods approach, including surveys and focus group discussions, the study compares the socio-economic conditions of cooperative members and non-members while evaluating the effectiveness of services provided by these cooperatives. The findings indicate that cooperative membership significantly improves household income, particularly from agricultural activities, although overall family income effects remain modest. The study also reveals that cooperatives primarily focus on financial services rather than marketing or production support. Recommendations include strengthening institutional frameworks, diversifying service offerings, and fostering inclusive governance structures to maximize the potential of agricultural cooperatives in poverty alleviation and rural development.